2014
DOI: 10.5455/aim.2014.22.156-159
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Initial Conditions on Reproducibility of Scientific Research

Abstract: Background:It is estimated that about half of currently published research cannot be reproduced. Many reasons have been offered as explanations for failure to reproduce scientific research findings- from fraud to the issues related to design, conduct, analysis, or publishing scientific research. We also postulate a sensitive dependency on initial conditions by which small changes can result in the large differences in the research findings when attempted to be reproduced at later times.Methods:We employed a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…(In a binary logistic regression predicting replication success, we entered contextual sensitivity, subdiscipline, and their interaction as predictors. Simple effects analysis via dummy coding demonstrated that the effect of contextual sensitivity was nearly identical in magnitude for social psychology studies [odds ratio (OR) = 0.823] and cognitive psychology studies [OR = 0.892]) In other words, contextual sensitivity appears to play an important role in replication success across multiple areas of psychology, and there is good reason to believe the effect of contextual sensitivity applies to other scientific fields as well (80,81).…”
Section: Resultsmentioning
confidence: 99%
“…(In a binary logistic regression predicting replication success, we entered contextual sensitivity, subdiscipline, and their interaction as predictors. Simple effects analysis via dummy coding demonstrated that the effect of contextual sensitivity was nearly identical in magnitude for social psychology studies [odds ratio (OR) = 0.823] and cognitive psychology studies [OR = 0.892]) In other words, contextual sensitivity appears to play an important role in replication success across multiple areas of psychology, and there is good reason to believe the effect of contextual sensitivity applies to other scientific fields as well (80,81).…”
Section: Resultsmentioning
confidence: 99%
“…In-depth analysis of the robustness of these relations is therefore contributing to the quality of information provided by them. A similar proposal, in the context of reproducible research, is presented in Djulbegovic and Hozo (2014). Overall, this work is about increasing the quality of information provided by a BN.…”
Section: Discussionmentioning
confidence: 94%
“…16 Of particular importance is the ability to define unambiguously the initial conditions prevailing when the process was performed. 17 Perhaps most critically is the way in which research is actually disseminated and reproduced.…”
Section: The Current State Of Automationmentioning
confidence: 99%